Dibalik Fakta dan Mitos Fenomena Super Blue “Blood” Moon - Yunina Surtiana (Undiksha, 2018)
This article discusses a natural phenomenon namely Super Blue (Blood) Moon (later to be referred as SBBM) in terms of scientific and mythical points of view. The method used in this study is literature study promoting library research as its instrument.Thus, as much literature as possible in a variety of types such as books, journals, and any articles is collected and later analyzed. Having synthesized the literature, this study finds out that in terms of science, it is a very phenomenal occurrence since there are three natural phenomena namely super moon, blood moon, and blue moon happening simultaneously. Researchers and scientists usually seize this moment for science. For instance, some of them study the temperature shift of the moon. In the meantime, in terms of mythical point of view, some beliefs starting from the moon fights with the sun, the moon is eaten by a dragon, and the moon contributes to maternal fertility, still exist among people around the world. In conclusion, there needs to be further socialization that SBBM is a scientific phenomenon and that it has nothing to do with the existing myths around the globe.